(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Inflammation and rheumatoid arthritis (RA) are complex physiological and pathological processes that significantly impact global health. While conventional treatments such as NSAIDs and disease-modifying anti-rheumatic drugs offer symptomatic relief, their long-term use is often associated with adverse effects. This review highlights the anti-inflammatory and anti-arthritic potential of various medicinal plants, emphasizing their bioactive constituents—such as flavonoids, alkaloids, terpenoids, and saponins—that modulate key inflammatory pathways including COX-2, NF-κB, and cytokine signaling. Numerous plant extracts, demonstrate significant efficacy in experimental models of inflammation and arthritis. The findings underscore the promise of phytochemicals as safer, multi-targeted alternatives for managing chronic inflammatory conditions and autoimmune disorders like RA.